Use of Financial Emergency Aid for adults with type 1 diabetes during COVID-19 pandemic in Brazil, 2020 (Research, Society and Development, 2022)
Objective: We sought to analyze the use of financial emergency aid in the acquisition of inputs for treatment by adults with Type 1 Diabetes during social distancing due to the pandemic of COVID-19 in Brazil. Method: Cross-sectional survey carried out during July 2020, in Brazil, using an online form about socioeconomic, demographic, glycemic monitoring and input acquisition. Pearson's Chi-Square test was applied, with adjusted residual analysis (p